2019
DOI: 10.1563/aaid-joi-d-18-00097
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Implantitis and Peri-Implant Mucositis Case Definitions in Dental Research: A Systematic Assessment

Abstract: The aim of this review was to determine the most common peri-implant mucositis and peri-implantitis case definitions used worldwide in the implant dentistry literature. A systematic assessment of peri-implant disease classification was conducted using all publications in MEDLINE, EMBASE, SCOPUS, and Google Scholar between 1994 and November 2017. Screening of eligible studies and data extraction were conducted in duplicate and independently by 2 reviewers. The search protocol identified 3049 unique articles, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…Although several studies in the literature reported an association between hypertension and periodontal diseases [27][28][29], we found that subjects with reported hypertension, who were living in areas where median household income was high, having lower bone loss compared to individuals who were living in areas where median household income was low. This is also supporting to the observation that individuals with high household income experienced lower difference in mean bone loss, which may indicate that access to healthcare system plays an important role by reducing the adverse effect of the outcome even among individuals who have predisposing conditions that put them at higher risk of the disease [30][31][32][33][34][35]. Nevertheless, limitations exist in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Although several studies in the literature reported an association between hypertension and periodontal diseases [27][28][29], we found that subjects with reported hypertension, who were living in areas where median household income was high, having lower bone loss compared to individuals who were living in areas where median household income was low. This is also supporting to the observation that individuals with high household income experienced lower difference in mean bone loss, which may indicate that access to healthcare system plays an important role by reducing the adverse effect of the outcome even among individuals who have predisposing conditions that put them at higher risk of the disease [30][31][32][33][34][35]. Nevertheless, limitations exist in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The local delivery of 1% alendronate gel was also examined in patients with aggressive periodontitis (a more severe form of periodontal disease [32], and diabetic patients with chronic periodontitis (a systemic disease that is associated with a higher risk of developing periodontal diseases [33], as an adjunct to scaling and root planing for the treatment of intrabony defects. The researchers of both studies found a significant reduction in probing depth, greater gain of clinical attachment level, and bone reforming of intrabony defects.…”
Section: Discussionmentioning
confidence: 99%
“…Our primary outcome is the level of alveolar bone on mesial and distal sites of posterior teeth as a continuous variable. We also categorized amount of bone loss based on case definition by the American Academy of Periodontology (AAP) into mild, moderate, and severe periodontitis [3941] to estimate the prevalence of each case definition for descriptive and baseline characteristics.…”
Section: Methodsmentioning
confidence: 99%